Criminogenic Policy Antithetical to Peace Policy: A Case Study of NAFTA as a Violation of International Law. Issue 3 (August 2021) - Patten, Daniel
Successful peace policy that enshrines human rights allows individuals to thrive economically, politically, and socially with minimal conflict. Building from literature on crimes of globalization, genocide, and human rights, the current research investigates the concept of a criminogenic policy that at its core is antithetical to peace policy. Using case study analysis, North American Free Trade Agreement (NAFTA) is found to be both criminal and criminogenic in violation of international law for two primary reasons. First, the NAFTA negotiation process was criminal and criminogenic for three interrelated reasons: (1) powerful elites heavily influenced the outcome, (2) it was undemocratic, and (3) the opposition was often repressed. Second, the NAFTA policy itself was criminal and criminogenic for two reasons: (1) NAFTA as a policy ignored all of the critical voices that predicted negative outcomes and (2) the written text of NAFTA is criminal for failing to include human rights protections while offering a litany of rights to protect business investment.